UPNEC performance management system using the balanced scoreboard - Pacia, Adeline A. (Philippine Engineering Journal)
The University of the Philippines National Engineering Center (UP-NEC) has been mandated through P.D. 1295 to fortify the country's continuing efforts at national development. In order to achieve this, the UP-NEC aims to provide technical training to ensure a steady and expanding supply of technical manpower with expertise in the various fields of technology and engineering; as well as, to develop technologies for the sustainable utilization of indigenous resources that address the needs of the local industry. In pursuit of this mandate, UP-NEC applied for and was awarded the Philippine Quality Challenge (PQC) Level 1 in 2012 and the Philippine Quality Award (PQA) Level 1 in 2016. PQA is not only a national recognition for exemplary performance, it also stimulates local companies and organizations to improve quality and productivity in fulfilling its mandate and its vision to be the HUB of Engineering Innovations and Technology. The findings and recommendations from the PQA Team of Assessors identified UP-NEC's strengths as well as opportunities for improvement. With the assessment, it was deemed that a more strategic performance assessment is needed to ensure that UP-NEC is able to fulfill its mandate and its vision. The Balance Scorecard was chosen as the performance measurement and strategy management system to align its strategic objectives of Service, Reach and Self-sufficiency with the attainment of goals for the employees and partners, effective internal processes, service to its clients and stakeholders as well as financial sustainability. The study discusses the National Engineering Center's (UP-NEC) proposed Balanced Scorecard strategies and initiatives to attain its strategic objectives and move towards being a true hub of engineering innovations and technology in support of the country's continuing efforts at national development.